PERSEPSI KOMUNIKASI LINTAS BUDAYA MASKULINITAS GENDER MENGENAI FEMINITAS BOYBAND KPOP - Infadillah, Rury; Azhar, Anang Anas; Zuhriah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research discusses the results of cross-cultural communication discussions that took place in the Medan ARMY community regarding the femininity displayed by BTS. So we get the result that masculinity is BTS's gender identity displayed by the media regarding BTS' feminine appearance, giving rise to a reconstruction of femininity among fans and the wider community. In it there are differences in understanding what femininity and masculinity actually are and how they respond to each of them which becomes an obstacle in the process of cross-cultural communication that exists. According to fans, the rearrangement of the meaning of femininity displayed by BTS creates an alienation of local culture from global culture. The feminine appearance displayed by BTS is considered by Indonesian society to be a social deviation and has a negative impact on Indonesia's young generation. Social construction among Indonesian society regarding femininity and masculinity is a marker of someone's appearance as a gender identity, but this is denied by some groups who think that a person's appearance does not have to be limited by gender. A person has the right to look as comfortable as possible without having to be limited by social constructions that exist in society, as well as the formation of standards from various groups and environments.